2013
DOI: 10.1182/blood.v122.21.3636.3636
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Randomized, Double-Blind, Placebo-Controlled Trial Demonstrating Reversal Of Rivaroxaban-Induced Anticoagulation In Healthy Subjects By Andexanet Alfa (PRT064445), An Antidote For Fxa Inhibitors

Abstract: Background Direct factor Xa inhibitors have demonstrated compelling anticoagulant efficacy and/or safety profiles across multiple diverse patient populations. A specific antidote to reverse anticoagulation during episodes of serious uncontrolled bleeding or before urgent/emergent surgery is lacking. Andexanet alfa (proposed INN)(AnXa, PRT064445) is a modified, recombinant human fXa molecule that is catalytically inactive but retains high-affinity binding to direct fXa inhibitors. It thus acts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Additionally, with reversal agents for oral direct anti-Xa anticoagulants on the horizon, the quantitative assessment offered by antifactor Xa testing could theoretically have a role in helping determine the necessity, dose, or duration/need for repeated dosing of reversal therapy. 2325…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, with reversal agents for oral direct anti-Xa anticoagulants on the horizon, the quantitative assessment offered by antifactor Xa testing could theoretically have a role in helping determine the necessity, dose, or duration/need for repeated dosing of reversal therapy. 2325…”
Section: Discussionmentioning
confidence: 99%
“…Many studies are being undertaken to find reversal agents for Factor Xa inhibitors. 46 48 One such drug, PRT445, has undergone Phase I and Phase II studies, which have confirmed it has a good safety profile in healthy volunteers. 48 Further studies are eagerly awaited.…”
Section: Management Of Bleeding Eventsmentioning
confidence: 98%
“…Andexanet alfa, developed by Portola Pharmaceuticals, is a recombinant FXa decoy effective against a wide range of anticoagulants including betrixaban, rivaroxaban, apixaban, enoxaparin, and fondaparinux. The modification of serine at position 419 to an alanine disables function of FXa while allowing for binding to heparin–AT complexes. A second modification involving removal of a carboxyglutamic acid membrane binding domain, GLa, prevents incorporation into the prothrombinase complex.…”
Section: Polyanions That Inhibit Blood Coagulationmentioning
confidence: 99%